KEPASTIAN HUKUM BAGI WARGA NEGARA ASING PELAKU TINDAK PIDANA DI AREA IMIGRASI - Fathur Rohman Brasal (2021)
With the presence of foreign nationals in Indonesia, it can be found that criminal acts committed by those foreign nationals. In fact, it could be that the intention to commit these violations already existed while still in their country and / or other countries. The purpose of this research is to find out and study the arrangements for foreign citizens (WNA) who commit criminal acts in the immigration area and to find out the arrangements for foreigners who perpetrate a criminal offense in the immigration area. This research is a normative juridical study, using a descriptive analytical approach. The research result are, To tackle transnational crime, a multilateral mechanism has been created through an international treaty which becomes the basic guide for countries in efforts to combat transnational crime. The Indonesian government in providing legal services in the field of immigration to the community has laid good foundations with the passing of the Law on Immigration which is considered capable of answering the aspirations of the community. Legal arrangements for foreigners who commit criminal acts in the immigration area are in accordance with the prevailing laws and regulations in Indonesia and are carried out in accordance with applicable law through the criminal justice system and if proven in court in court to commit acts that fulfill the elements of a criminal act, then criminal sanctions in accordance with the laws and regulations, it will be imposed on foreigners, including those who may be refused or expelled. Keyword; Immigration,Foreign Citizens, Crime, Immigration Area